Implementasi Nilai – Nilai Karakter Bangsa Oleh Peserta Didik Di Dalam Kurikulum Merdeka - Albin Dwi Cahya (Universitas Palangka Raya, 2025)
We conducted research in schools to find out how the values of national character are implemented in the independent curriculum. National character must always exist even though the curriculum itself often changes. The values of national character that we have should not just disappear, but we must always guard them so that they are not lost. The independent curriculum certainly has done a lot to preserve the values of national character so that students can know what the values of national character are. For the research method itself, I used qualitative research methods by means of interviews and observations. In the schools where we conducted research, namely at SMAN 4 Cibinong and SMPN 4 Kota Serang, we have implemented national character values in the independent curriculum in the implementation of learning, namely honesty, creativity and religious values, for this reason we are also carrying out research activities this time focuses more on students implementing the values of our national character. Students must always apply the character values of the Indonesian nation in implementing the independent curriculum that is currently being implemented.